2015
DOI: 10.1007/s00894-015-2649-6
|View full text |Cite
|
Sign up to set email alerts
|

The bond force constant and bulk modulus of small fullerenes using density functional theory and finite element analysis

Abstract: Dedicated bond force constant and bulk modulus of C n fullerenes (n = 20, 28, 36, 50, 60) are computed using density functional theory (DFT). DFT predicts bond force constants of 611, 648, 675, 686, and 691 N/m, for C20, C28, C36, C50, and C60, respectively, indicating that the bond force constant increases for larger fullerenes. The bulk modulus predicted by DFT increases with decreased fullerene diameter, from 0.874 TPa for C60 to 1.830 TPa for C20. The bond force constants predicted by DFT are then used as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…The Bulk modulus value obtained in the current work shows a 26.76% difference with the results of the bond force method by Ruoff and Ruoff [22], due to the fact that this model only consider axial bond forces. Differences with the current Bulk modulus calculations are 16.90% for the Tapia et al model [24] based on linear spring finite element analysis, and 109.86% for the spring-based method proposed by Giannopoulos et al [26]. The use of the second spring element to simulate the bending interaction by Giannopoulos et al explains the large difference observed.…”
Section: Fullerenes Bulk Modulusmentioning
confidence: 80%
See 3 more Smart Citations
“…The Bulk modulus value obtained in the current work shows a 26.76% difference with the results of the bond force method by Ruoff and Ruoff [22], due to the fact that this model only consider axial bond forces. Differences with the current Bulk modulus calculations are 16.90% for the Tapia et al model [24] based on linear spring finite element analysis, and 109.86% for the spring-based method proposed by Giannopoulos et al [26]. The use of the second spring element to simulate the bending interaction by Giannopoulos et al explains the large difference observed.…”
Section: Fullerenes Bulk Modulusmentioning
confidence: 80%
“…Analyzing now the influence of fullerene size, Fig. 7 shows the Bulk modulus in function of fullerene radius obtained with different techniques: the spring-based method (SBM) [26], the spring finite element analysis (SFEA) [24], the density functional theory (DFT) [24] and the BBM implemented in this work. We can see that all the results exhibit the same tendency, where the Bulk modulus decreases as the radius increases.…”
Section: Fullerenes Bulk Modulusmentioning
confidence: 99%
See 2 more Smart Citations
“…Then, the bulk modulus (B) calculated by the he relationship between the total molecular energy (E) and the volume change (ΔV) around the equilibrium volume (V 0 ): 66 , 67 , 68 …”
Section: Methodsmentioning
confidence: 99%